2004
DOI: 10.1111/j.0904-2512.2004.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Central giant cell granuloma of the jaws: assessment of cell cycle proteins

Abstract: Cyclin D1 protein overexpression may be involved in the formation of the giant cells and the pathogenesis of central giant cell granuloma. As the distribution of immunostaining is identical to that observed in giant cell tumor of bone, our results support the possibility that central giant cell granuloma of the jaws and giant cell tumor of bone represent a similar disease process that clinically and histologically may have somewhat different features because of differences in the anatomical site of involvement. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 21 publications
(22 reference statements)
4
34
0
2
Order By: Relevance
“…The pathogenetic significance of these proteins in the development of other neoplasms has been an area of discussion for considerable time [52,60]. An over-expression of the cell cycle regulating protein cyclin D1 was established in GCT and in the central giant cell granuloma of the jaw [20]. Of particular note in this study is the fact that there was an over-expression of cyclinD1-mRNA and an increase in the cyclinD1 protein, particularly in the nuclei of the MNGC.…”
Section: Additional Pathogenetic Factors In Gctmentioning
confidence: 66%
“…The pathogenetic significance of these proteins in the development of other neoplasms has been an area of discussion for considerable time [52,60]. An over-expression of the cell cycle regulating protein cyclin D1 was established in GCT and in the central giant cell granuloma of the jaw [20]. Of particular note in this study is the fact that there was an over-expression of cyclinD1-mRNA and an increase in the cyclinD1 protein, particularly in the nuclei of the MNGC.…”
Section: Additional Pathogenetic Factors In Gctmentioning
confidence: 66%
“…For example, in a previous study we have shown little difference in terms of cycle markers between these two entities. 30 However, the absence of p63 expression in central giant cell granuloma suggests these tumors may have a pathogenesis that differs from that of giant cell tumor of bone. Interestingly, the giant cell component of giant cell tumor of salivary gland has similar histological features to giant cell tumor of bone, but does not express p63, 31 lending support to suggestions that this tumor is also unrelated to giant cell tumor of bone.…”
Section: Discussionmentioning
confidence: 99%
“…However, the possibilities that some subtypes of CGCG of the jaws (e.g. those associated with syndromes) may represent a neoplastic process 21,22 , akin to the giant cell tumor of bone, 23,24 or have a systemic component, 25 has not been conclusively ruled out.…”
Section: Case Presentationmentioning
confidence: 99%